Celebrating Islam and Multiculturalism in New Zealand - Ropi, Ismatu (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2013)
Syarif Hidayatullah State Islamic University (UIN) Jakarta in collaboration with the Embassy of New Zealand in Jakarta, the Asia New Zealand Foundation and the International Office of UIN Jakarta on 20 to 24 May 2013 held a photographic exhibition documenting the stories of Asian Muslims in the Kiwi Island, and a half-day discussion of a book by Adrienne Jansen and Ans Westra entitled “The Crescent Moon: The Asian Face of Islam in New Zealand”.DOI: 10.15408/sdi.v20i2.392